Penerapan Konsep Lean Service Untuk Perbaikan Pelayanan Servis Mobil Di Auto2000 Basuki Rahmat Surabaya - Adelia Hernalis Agustin; Dwi Sukma Donoriyanto (Jurnal Kendali Teknik dan Sains, 2023)
AUTO2000 Basuki Rahmat is one of the branches dealer Toyota, which is located in the city of Surabaya, is engaged in services such as sales, maintenance, repair and supply of Toyota spare parts whose management is fully handled by the Astra Group. The company always strives to provide fast and accurate service, but customers spend quite a long time waiting because the car service process is relatively long. The long service time is caused by an unorganized operational system that causes waste (waste). Based on these problems, it is necessary to analyze Basuki Rahmat's car service services at AUTO2000 using the concept lean service by using the method value stream mapping, fishbone, and 5 whys. The research results obtained weight waste motion or transportation of 0.1481; waiting or delay of 0.1325; incorrect inventory of 0.1273; lack of customer’s focus of 0.1195; defect of 0.1065; duplication of 0.0935; overproduction of 0.0779; unclear communication of 0.0675; underutilized employees of 0.0675; And variation of 0.0597. Research recommendations that can be proposed to reduce waste including repairs layout, adding monitors on the service floor for matters of sending and receiving information, increasing the number of mechanics, making plans booking with different hours, making and applying the system tracking of the presence of the tool. Therefore, lead time the initial service service process of 170 minutes becomes lead time 128 minutes.